Verification techniques for sensitivity analysis and design of controllers for nonlinear dynamic systems with uncertainties - Rauh, Andreas; Minisini, Johanna; Hofer, Eberhard P. (Zielona Góra: Uniwersytet Zielonogórski)
Control strategies for nonlinear dynamical systems often make use of special system properties, which are, for example, differential flatness or exact input-output as well as input-to-state linearizability. However, approaches using these properties are unavoidably limited to specific classes of mathematical models. To generalize design procedures and to account for parameter uncertainties as well as modeling errors, an interval arithmetic approach for verified simulation of continuous-time dynamical system models is extended.
Keywords: interval arithmetic; reachability analysis; observability analysis; robust stability; model-based design of optimal controllers